CONVERSATIONAL IMPLICATURE IN DEN OF DRAGONS’ DRAMA SCRIPT - Dwi Iswahyuni (IKIP Siliwangi, 2022)
This study strives to disclose the conversational implicature in a drama script. The objective of the study was to discover what conversational maxims flouted to yield conversational implicature in a drama script entitled “Den of Dragons”. The research method used in this study is a descriptive qualitative method. In undertaking the analysis, this study employs Grice’s theory about conversational implicature. The findings showed that from thirty nine excerpts, the number of non-observance of the maxims, especially flouting the maxims, was eighteen excerpts and the rest belonged to observing the maxims. The number of flouting the maxims of Quantity, Quality, Relation, and Manner respectively were nine, three, five, one. In conclusions, the conversational maxims flouted in this drama script are maxims of Quantity, Quality, Relation, and Manner. Furthermore, the most dominant flouting maxim is flouting the maxim of Quantity and the rarest occurrence belongs to flouting the maxim of Manner. In accordance with flouting the maxim of Quantity, the utterances said by the characters are less or more informative than what are required or expected. Keywords: Conversational Implicature, Den of Dragons